Diseño de una línea de producción de envases biodegradables a partir de bioplástico, aprovechando residuos del plátano (musa paradisiaca) con aplicación para el uso de empaquetado de alimentos - Calero Zurita, Mabel Fabiola (2021)
The main objective of the research project was the design of a production line for biodegradable packaging based on the waste of banana peels (Musa paradisiaca). The manufacture of petroleum-based plastics has become a polluting material for the environment and with a long degradation time, causing a very serious risk for nature. For this reason, a solution is sought with the creation of bioplastics that have a short degradation time, but with higher production costs than existing polymers. Eight experimental units were analyzed for both starch and bioplastic using as main raw material the shells of Musa paradisiaca and Musa cadavendish L, the analyzes were of yield, ash and moisture for starch; Bioplastic films were analyzed for pH, humidity, density, thickness and biodegradation. In this research, the starches extracted from said banana peels were taken as raw material, which were combined with glycerin, agar-agar, sodium benzoate and acetic acid. The films obtained with these mixtures were physically tested to determine which of the treatments has the best characteristics, fearing v1m0 as a result. With the elaboration of the bioplastic, a production line was designed that consisted of the elaboration of flow diagrams and routes from the arrival of the waste from the shells to obtaining the container, an AMFE matrix was made to determine the controls and inspection both to the product as well as to the process, an MRP of the requirements of the materials, the realization of a balance line to determine the performance and an analysis of the relationship of the activities. The machines that will be used in the process and the areas where they will be taking into account the operations. Keywords: Bioplastic, banana peels, starch, biodegradation, production line.